A systematic analysis of and recommendations for public health events involving brucellosis from 2006 to 2019 in China. (31st December 2022) - Liu, Zhiguo; Wang, Miao; Tian, Yaxin; Li, Zhongqiu; Gao, Liping; Li, Zhenjun
Abstract: Brucellosis is a severe public health problem in China. However, analysis on related infection events is lacking. We performed a systematic analysis of brucellosis laboratory infection and vaccine infection events from 2006 to 2019 in China based on the published literatures. Our analysis showed that most laboratory Brucella infections in hospitals were found in Southern China. The identification and handling of suspected samples of Brucella infection without following the recommended biosafety protection was the main risk factor. It is important to strengthen the preventive awareness of clinical laboratory staff and physicians, while highlighting the compulsory handling and identification of suspected Brucella -infected samples in biosafety facilities and following biosafety practices. However, a severe Brucella infection accident at the Northeast Agricultural University, with 28 positive cases, showed that strengthening the management in teaching experiments of students in the veterinary-related profession is essential. However, cluster S2 vaccine strain infection events caused by vaccination and production were mainly observed in Northern China. Strengthening vaccination skills, personal protection, and improving the biosafety management of vaccine production and implementing regular risk surveillance is mandatory. Our analysis provides helpful clues for control of public health events involving brucellosis, as well as implementing intervention strategies is urgent.